The Role of IL-35 in the Pathophysiological Processes of Liver Disease - Hu, Shuang; Lian, Pan-pan; Hu, Ying; Zhu, Xing-yu; Jiang, Shao-wei; Ma, Qiang; Li, Liang-yun; Yang, Jun-fa; Yang, Li; Guo, Hai-yue; Zhou, Hong; Yang, Chen-chen; et al. (Frontiers in Pharmacology, 2021)
It is known that liver diseases have several characteristics of massive lipid accumulation and lipid metabolic disorder, and are divided into liver inflammation, liver fibrosis, liver cirrhosis (LC), and hepatocellular carcinoma (HCC) in patients. Interleukin (IL)-35, a new-discovered cytokine, can protect the liver from the environmental attack by increasing the ratio of Tregs (T regulatory cells) which can increase the anti-inflammatory cytokines and inhibit the proliferation of immune cellular. Interestingly, two opposite mechanisms (pro-inflammatory and anti-inflammatory) have connection with the ultimate formation of liver diseases, which suggest that IL-35 may play crucial function in the process of liver diseases through immunosuppressive regulation. Besides, some obvious advantages also imply that IL-35 can be considered as a new therapeutic target to control the progression of liver diseases, while its mechanism of function still needs further research.